The use of reflective practice in teaching: a case study of in-service primary english language excellent teachers - Siti Noor Aneeis, Hashim (2021)
Reflective practice is an important part in the teaching and learning processes. It enables the teachers to observe, evaluate and make changes towards effective practices. The use of reflective practice in teaching allows the teachers to have continuous personality and professional development to cope with the nature of work which is changing rapidly. As a consequence, English language teachers can no longer focus on transmitting pieces of information but they must reflect to help the students to learn more meaningfully. As such, this will enable them to accomplish the demands of education which is to upgrade the learners’ quality in line with the aspirations of the National Education Philosophy. Although, reflective practice is recognised as a part of teaching, not all teachers adapt reflective practices in their teaching due to lack of reflective skills, support and guidelines on how to use reflective practice in their teaching. Therefore, this qualitative case study sought to explore the process of using reflective practice in teaching among six in-service English language teachers from four cluster primary schools situated in a northern state in Peninsula Malaysia based on four research questions. The participants were selected via purposive sampling. Data were gathered in four phases through semistructured interviews, document analysis and field notes to answer four fundamental research questions. The software NVivo 11 was used in managing and analysing data to form emerging themes. The themes were named (a) the nature of teachers’ reflections, (b) the dynamics of teachers’ reflective actions, (c) cognitive, behavioural and working culture impediment clusters and (d) developing self-reflection. A practical framework and set of guidelines were developed based on the findings to propose applicable and practical principles grounded in the Malaysian context for the teachers to use reflective practice in enhancing their teaching practice and improving students’ learning.